Prospective cohort study of persistent hypertension following pre-eclampsia at Medani Hospital, Sudan. Issue 1 (July 2016) - Fadalallah, Zubaida M.; Elhassan, Elhassan M.; Rayis, Duria A.; Abdullahi, Hala; Adam, Ishag
Abstract: Objective: To evaluate the incidence of, and factors associated with, persistent hypertension in patients with pre-eclampsia. Methods: A prospective cohort study enrolled patients presenting with pre-eclampsia at Wad Medani Maternity Hospital, Sudan, between March 1 and October 31, 2014. Obstetric, clinical, and biochemical variables were recorded at presentation and at 6 weeks after delivery. Results: Of 188 patients enrolled in the study, 6-week follow-up data were available for 165. Among these patients, 136 (82.4%) and 29 (17.6) had mild and severe pre-eclampsia, respectively. At 6-week follow-up, 58 (35.2%) patients were experiencing persistent hypertension. Patients with persistent hypertension demonstrated significantly lower platelet counts at baseline ( P  = 0.001) and neonatal weight at delivery ( P  < 0.001) than patients who were normotensive at 6 weeks. Severe pre-eclampsia was more common among patients who experienced persistent hypertension than those who were normotensive 6 weeks after delivery ( P  < 0.001). In a logistic-regression analysis, none of the investigated factors was associated with persistent hypertension; however, patients experiencing severe pre-eclampsia were 7.3-times more likely to experience persistent hypertension than patients with mild pre-eclampsia (95% confidence interval 1.6–32.2; P  = 0.008). Conclusion: Persistent hypertension 6 weeks after delivery was common among patients who experienced pre-eclampsia in Sudan (particularly severe pre-eclampsia) regardless of patients' age and parity.